„Cywilizowanie” usług hotelarskich przez administrację - Pieprzny, Stanisław; Ura, Elżbieta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The aim of the study is to draw attention to the scope of administrative and legal forms of action of public administration authorities in relation to the sphere of hotel services. Regulations in this area are included in the law on tourist services. The legislator regulates the types and categories of hotel facilities and provides minimum standards for facilities that are not included in the law for hotel facilities in which hotel services may also be provided. The basic legal form of action of the administration is the administrative decision, for example, the classification to the category and type of the hotel. Attention was also drawn to the special kind of administrative decision, which may be issued to the entrepreneur conducting hotel services, administrative promiscuity (promise). An important function in the sphere of hotel services is provided by control authorities because it forces entrepreneurs to maintain an appropriate level of service, according to the administrative grade of the hotel, and provides clients with the ability to enforce a specific level of service.
Keywords: the principle of hospitality; legal forms of administrative action; administrative authorities; obligations of the entrepreneur; hotel facilities; hotel services